2018
DOI: 10.1111/all.13418
|View full text |Cite
|
Sign up to set email alerts
|

Identification of T‐cell epitopes from benzylpenicillin conjugated to human serum albumin and implication in penicillin allergy

Abstract: This study identifies and characterizes for the first time the BP-haptenated peptides from HSA involved in the immunization of patients to penicillins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 37 publications
2
48
0
3
Order By: Relevance
“…This test measures the T cell proliferation to a drug in vitro, from which one can simulate a previous in vivo reaction against a drug sensitization. Lymphocyte transformation test has been widely implemented for medical diagnosis of immunodeficiency, pathogenic diseases, and type IV allergy (40,41). The Rainger and Rowley (42) was used to determine the serum bactericidal activity to Aeromonas hydrophila strain, and the results were expressed as survival index.…”
Section: Immune Indicesmentioning
confidence: 99%
“…This test measures the T cell proliferation to a drug in vitro, from which one can simulate a previous in vivo reaction against a drug sensitization. Lymphocyte transformation test has been widely implemented for medical diagnosis of immunodeficiency, pathogenic diseases, and type IV allergy (40,41). The Rainger and Rowley (42) was used to determine the serum bactericidal activity to Aeromonas hydrophila strain, and the results were expressed as survival index.…”
Section: Immune Indicesmentioning
confidence: 99%
“…Recently, important advances have been performed regarding the understanding of sensitization and haptenation process of BLs. A study has identified two target peptides of human serum albumin (HSA) for benzylpenicillin, to which this drug was covalently bound on lysines 159 and 525, which were able to induce specific proliferation of T cells from BL‐allergic patients . Another study has suggested that patients could be immunized by benzylpenicillin‐haptenated peptides from proteins generated in dendritic cells during the processing and presentation to T cells .…”
Section: New Understanding Of Dhr Mechanismmentioning
confidence: 99%
“…A study has identified two target peptides of human serum albumin (HSA) for benzylpenicillin, to which this drug was covalently bound on lysines 159 and 525, which were able to induce specific proliferation of T cells from BL-allergic patients. 140 Another study has suggested that patients could be immunized by benzylpenicillin-haptenated peptides from proteins generated in dendritic cells during the processing and presentation to T cells. 141 Moreover, CLV binds to Lys 195 and 475 residues of HSA, forming adducts able to activate basophils in 69% of CLV-allergic patients.…”
Section: Ige-mediated Reactionsmentioning
confidence: 99%
“…We have also recently identified BP‐haptenated peptides from HSA that can activate naïve CD4+ T cells . Two of these BP‐haptenated peptides were also found to induce PBMCs proliferation in allergic patients confirming their role in patients immunization …”
Section: Introductionmentioning
confidence: 99%